y = 4x + 4
y = -3x - 3
-------------------------------------------------------------------------------------------------------------------
Note that both of them are equal to y, so you can set them equal to each other
4x + 4 = -3x - 3
Isolate the x. Add 3x to both sides, and subtract 4 from both sides
4x (+3x) + 4 (-4) = -3x (+3x) - 3 (-4)
4x + 3x = -3 - 4
Simplify
7x = -7
Isolate the x. Divide 7 from both sides
7x/7 = -7/7
x = -7/7
x = -1
-------------------------------------------------------------------------------------------------------------------
Plug in -1 for x in one of the equations.
y = 4x + 4
y = 4(-1) + 4
y = -4 + 4
y = 0
-------------------------------------------------------------------------------------------------------------------
x = -1, y = 0, or A) (-1,0) is your answer
hope this helps